Pharmacokinetics of Pimobendan and Its Metabolite O-Desmethyl-Pimobendan Following Rectal Administration to Healthy Dogs - Her, Jiwoong; Kuo, Kendon W.; Winter, Randolph L.; Cruz-Espindola, Crisanta; Bacek, Lenore M.; Boothe, Dawn M. (Frontiers in Veterinary Science, 2020)
Objective: To describe the pharmacokinetics of parent pimobendan (PIM) and its active metabolite, o-desmethyl-pimobendan (ODMP), after oral and rectal administration of pimobendan to healthy dogs. Animals: 8 healthy privately-owned dogs. Procedures: Dogs received a single dose (0.5 mg/kg) of a commercially available pimobendan tablet per os (PO). Twelve blood samples were collected over a 12-hour period for pharmacokinetic analysis. After 24 hours washout period, dogs received the same dose of a pimobendan solution per rectum (PR), and samples were obtained at the same times for analysis. Results: For PIM, PO vs PR, respectively, mean maximum plasma concentration (Cmax, ng/mL) 49.1 ± 28.7 vs 10.1 ± 2, time to reach the maximum concentration (Tmax, h) 2.1 ± 0.9 vs 1 ± 0.4, disappearance half-life (t1/2, h) 1.8 ± 0.8 vs 2.2 ± 0.6, and area under the concentration-time curve (AUC, ng*h/mL), 148.4 ± 71.6 vs 31.1 ± 11.9, with a relative bioavailability (F, %) of 25 ± 8. For ODMP, PO vs PR, respectively, Cmax was 30.9 ± 10.4 vs 8.8 ± 4.8, Tmax 3.2 ± 1.6 vs 1.7 ± 1.1, t1/2 5.0 ± 2.7 vs 8.3 ± 4.8, with AUC 167.8 ± 36.2 vs 50.1 ± 19.2, with F of 28 ± 6. Differences between PO and PR were significant (P < 0.03) for AUC and Cmax for both PIM and ODMP. Conclusions and Clinical Relevance: Pharmacokinetics of PIM and ODMP were described following PO and PR administration. Findings suggest that pimobendan PR might achieve effective concentrations and as such warrant future studies of clinical effectiveness in treating dogs with congestive heart failure who are unable to receive medication PO.